Tracer Study Program Studi Administrasi Bisnis - eva yoyet; Primadona Primadona; Yosi Suryani; Ika Yuanita (Jurnal Ilmiah Poli Bisnis, 2020)
This study aims to find out what is needed by the company for prospective employees. Higher Education is a producer of labor so that what is produced must be in line with industry needs. This research was conducted by survey method using a questionnaire instrument. The number of respondents was 139 people who were spread out in all regions with respondents being alumni users or company owners / managers who had been alumni from 2014 to 2018. The results of the study revealed that there were some skills that alumni had to have, namely foreign language skills, personality good and in accordance with job specifications, the ability to use computer equipment, communication skills and others. This ability has special requirements for alumni in getting jobs both private companies and state-owned or civil servants. The limitation of this study is that the questions raised are limited to alumni users but there are still many other questions that should also be important for universities and for further research this can be done.